Exocyst subunits EXO70B1 and B2 contribute to stomatal dynamics and cell wall modifications - Drs, Matěj; Müller, Karel; Voxeur, Aline; Ortmannová, Jitka; Serrano, Natalia; Vernhettes, Samantha; Škrabálková, Eliška; Potocký, Martin; Žárský, Viktor; Pečenková, Tamara (Frontiers in Plant Science, 2025)
IntroductionBased on previous reports of defense-related defects in the Arabidopsis loss-of-function (LOF) mutants of the EXO70B1 and EXO70B2 exocyst subunits, we investigated the underlying causes of these phenotypes. MethodsWe analyzed stomatal aperture states in both young and adult plants. As the exocyst is involved in the secretion to the cell wall, we examined cell wall composition, and we correlated these findings via a comprehensive mRNA expression analysis. ResultsOur results revealed and discovered a more closed initial state of stomatal opening in exo70B mutants, as well as altered methylation and acetylation modifications of pectin and hemicellulose in the studied mutant lines. These changes in cell wall modifications may contribute to both compromised stomatal aperture-dependent and stomatal aperture-independent defense responses, as well as to the transcriptional activation of defense pathways observed in non-infected mutant plants at adult developmental stages. Several candidate genes involved in these processes were pinpointed using RNA-seq analysis.DiscussionInterestingly, although the primary phenotypic and RNA-seq deviations in young mutant lines may be specific for each of the two EXO70B mutant lines, they exhibit converging gene expression profiles in later developmental stages. This convergence may reflect the shared evolutionary origin of the two Brassicaceae EXO70 isoforms by duplication from a common ancestral gene.